Understanding Gait, Its Neurophysiologic Control and Systematic Localisation of Gait Abnormalities - Manokaran, Thaanesh; Yusoff, Muhammad Zikri; Mariyapan, Prehmanraj; Abdullah, Jafri Malin (Malaysian Journal of Medical Sciences, 2025)
Gait analysis is a crucial diagnostic tool in neurology and rehabilitation, reflecting the intricate coordination between the central and peripheral nervous systems, musculoskeletal structures, and sensory feedback mechanisms. This article integrates the neurophysiological basis of gait, emphasising the role of central pattern generators in the spinal cord and the mesencephalic locomotor region in regulating initiation, speed, and adaptability (1). Gait disorders result from disruptions in various neural structures, including the cerebellum, basal ganglia, motor and sensory pathways, and the peripheral nervous system (2). Functional gait disorders, characterised by inconsistent or exaggerated patterns, require differentiation from organic conditions (3). This article also highlights diagnostic tools, including motion capture systems, electromyography, and wearable sensors, as well as therapeutic interventions, such as physical therapy, pharmacological treatments, and emerging rehabilitative technologies (4).